Modality in Spanish and combinations of modal meanings - Kratochvílová, Dana (Charles University, Karolinum Press, 2018)
"This monograph focuses on modality in Spanish. It presents the theoretical approach to this category formulated by Bohumil Zavadil and, consequently, it analyses its possible application to Spanish. We concentrate on specific areas of the Spanish modal system where two modal meanings combine. Theoretical analyses are combined with corpus-based studies concentrating on the choice of mood or contextual interpretation of selected constructions. We veryfied that areas where two modal meanings meet are a natural part of the Spanish modal system and that the combination of modal meanings has consequences on the mood selection."--